RETURN ON EQUITY DAN DEBT TO EQUITY RATIO SEBAGAI DETERMINAN NILAI PERUSAHAAN: STUDI EMPIRIS PADA PERUSAHAAN BURSA EFEK - Pricillia Putri Sumadi; Tevi Leviany; R. Rita Avianty; Reksha Laksana (Universitas Sangga Buana, 2026)
Energy sector companies play a vital role in the Indonesian economy, but face challenges such as fluctuating commodity prices and environmental issues that require increased corporate value to attract investment. This study aims to analyze the impact of profitability (Return on Equity) and solvency (Debt to Equity Ratio) on the value of energy sector companies listed on the Indonesia Stock Exchange for the 2021–2023 period. This study uses secondary data from annual reports with a panel data regression approach, with 69 observations processed using EViews 13 and Microsoft Excel. The results indicate that, partially,Return on Equityhas a significant influence on company value, whereasDebt to Equity Ratiodoes not have a significant effect. However, simultaneously,Return on Equity And Debt to Equity Ratiohas a significant influence on company value. This study concludes that profitability is a major factor in shaping the value of energy sector companies.